2014
DOI: 10.2527/jas.2013-6890
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Miles City Line 1 on the United States Hereford population1,2,3

Abstract: The goal of this research was to document the influence of Line 1 (L1) Hereford cattle, developed by the USDA at its research facility in Miles City, MT, on the U.S. Hereford population. The L1 Hereford population originated in 1934 and has been thereafter maintained as a closed herd at that location. Dissemination of germplasm began in 1948. Pedigree data for approximately 14 million cattle recorded by the American Hereford Association (AHA) were used. A preliminary experiment was conducted to establish sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Within the US the breed is widely distributed across varying climatic zones. Although comparable levels of observed and expected heterozygosity have been reported for Hereford [41] and other Bos taurus breeds [42], high average genetic relationships have been observed in Herefords, suggesting genetic diversity maybe more limiting than in other breeds [29, 33]. …”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Within the US the breed is widely distributed across varying climatic zones. Although comparable levels of observed and expected heterozygosity have been reported for Hereford [41] and other Bos taurus breeds [42], high average genetic relationships have been observed in Herefords, suggesting genetic diversity maybe more limiting than in other breeds [29, 33]. …”
Section: Discussionmentioning
confidence: 63%
“…The inbred population Line 1 has had a significant effect on the Hereford breed and it has been estimated that 79% of the Herefords registered from 2006 to 2008 have some proportion of Line 1 in their pedigree [33]. Due to the large number of Line 1 animals sampled in the “2,000 Bull Project” and Line 1’s general influence among the Hereford breed a second series of analyses were performed to remove the excessive population bias from the dataset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data used in this study were from line 1 Hereford cattle at USDA-ARS, Fort Keogh Livestock and Range Research Laboratory, Miles City, MT (Knapp et al, 1951;MacNeil, 2009;Leesburg et al, 2014). A historical review of the formation and management of this herd is provided by MacNeil (2009).…”
Section: Animals Genotypes and Phenotypesmentioning
confidence: 99%
“…Pedigree analysis for the Herefords within each subpopulation indicated that the subpopulations comprised animals from the highly inbred USDA Miles City Line 1 Hereford population (L1) and other individuals representing broader U.S. Hereford pedigrees. Since the founding of the L1 Herefords, the migration of germplasm has been unidirectional from L1 into the broader U.S. industry, as the L1 population has been closed since its founding [18]. L1 Herefords do not segregate for recessive dwarfism, which has been a threat to Hereford breeders since the 1950s, and this has led to L1 cattle becoming popular in the process of purging herds of the defect [19].…”
Section: Resultsmentioning
confidence: 99%